Pediatric Evaluation of Disability Inventory Computer Adaptive Test (PEDI-CAT) and Alberta Infant Motor Scale (AIMS): Validity and Responsiveness. - Dumas, Helene M.; Fragala-Pinkham, Maria A.; Rosen, Elaine L.; Lombard, Kelly A.; Farrell, Colleen (Physical Therapy, 2015)
Background. Although preliminary studies have established a good psychometric foundation for the Pediatric Evaluation of Disability Inventory Computer Adaptive Test (PEDI-CAT) for a broad population of youth with disabilities, additional validation is warranted for young children. Objective. The study objective was to (1) examine concurrent validity, (2) evaluate the ability to identify motor delay, and (3) assess responsiveness of the PEDI-CAT Mobility domain and the Alberta Infant Motor Scale (AIMS). Methods. Fifty-three infants and young children (<18 months of age) admitted to a pediatric postacute care hospital and referred for a physical therapist examination were included. The PEDI-CAT Mobility domain and the AIMS were completed during the initial physical therapist examination, at 3-month intervals, and at discharge. A Spearman rank correlation coefficient was used to examine concurrent validity. A chi-square analysis of age percentile scores was used to examine the identification of motor delay. Mean score differences from initial assessment to final assessment were analyzed to evaluate responsiveness. Results. A statistically significant, fair association (rs=.313) was found for the 2 assessments. There was no significant difference in motor delay identification between tests; however, the AIMS had a higher percentage of infants with scores at or below the fifth percentile. Participants showed significant changes from initial testing to final testing on the PEDI-CAT Mobility domain and the AIMS. Limitations. This study included only young patients (<18 months of age) in a pediatric postacute hospital; therefore, the generalizability is limited to this population. Conclusions. The PEDI-CAT Mobility domain is a valid measure for young children admitted to postacute care and is responsive to changes in motor skills. However, further item and standardization development is needed before the PEDI-CAT is used confidently to identify motor delay in children <18 months of age.